(untitled) (ENTHYMEMA, 2010)
The 7th international Yasnaya Polyana conference, dedicated to the centenary of the escape and the death of Tolstoy, has been characterized by the several number of approaches chosen by the experts taking part in the experience. During the 3 days of the conference they have analyzed the impact of Tolstoy’s works and theories not only on a strictly literary scale, but also on other fields of knowledge, such as anthropology or philosophy, like in Slivickaya’s contribution on the «dynamic identity» of Tolstoy’s man or in Klimova’swork on the philosophical contents of the Strakhov-Tolstoy correspondence. The biographic aspect has been as well touched (in the controversial report by Zwiers on the tormented relationship between Tolstoy and his wife or Katz’s contribution on Tolstoy and Chertkov), along with the impact of Tolstoy’s texts on contemporary life, like in Olea’s work on the influence of the Russian writer on the American soldiers.